Population, ethics, and equity - Giovanni Berlinguer
Demography is impregnated, more or less explicitly, with ethical contents. This is apparent in the words used to support data, which change over time (e.g., the term "illegitimate child" is no longer used). Ethical principles must be analyzed because demography concerns both public policies and individual choice. There is a conflict in this area between the idea of the ethical state, dictating personal behaviors to citizens, and that of decisions based on freedom, supported by three shared values: human rights, pluralism, and equity. This paper examines how these could be reinterpreted in the context of choices regarding population.